Recent Advances in Synthesis of Functionalized β-Lactams through Cyclization of N-Propargyl Amine/Amide Derivatives - Vessally, Esmail; Babazadeh, Mirzaagha; Hosseinian, Akram; Edjlali, Ladan; Sreerama, Lakshmaiah (Current Organic Chemistry, 2018)
β-lactams have attracted a significant attention due to their potential biological activities and wide variety of synthetic applications. Developing novel and efficient methods for construction of functionalized β-lactams has been the subject of a number of papers in recent years. N-Propargyl amines/amides are one of the most specific class of alkynes having diverse reaction patterns. It is well known that they can undergo a number of cyclization reactions to produce various significant nitrogen containing heterocycles. This review surveys literature methods for the synthesis of highly substituted β-lactams from simple and easily available N-propargyl amine/amide derivatives from 1991 to 2017.
Keywords: N-propargylamides